(untitled) (SCHOLARS: Journal of Arts & Humanities, 2019)
This paper primarily presents the trajectory of growing up in South Asia drawing insights from the selected novels about South Asian youths (SA youths). In this process, the paper explores the political interest of the West in non-Western children and youths. The focus is on the exploration of whether contemporary youth literatures have still been reinforcing the image of SA youths as the Other of the European youths, or if there has been any significant change augmented by the recent phenomenon of global connectedness. By laying a framework of these forces for analyzing how they are reflected in the literatures for the South Asian youths by foreign, diaspora and home authors, this paper prepares a ground for further exploration.